Educational strategies and roles of stakeholders in reducing antisocial behavior of football supporters - Arifuddin Usman; Muhammad Adnan Hudain; M. Said Zainuddin; Gatot Jariono; Muhammad Miftah Fauzan (Jurnal Cakrawala Pendidikan, 2021)
This study aims to determine the strategies and roles of stakeholders in an effort to reduce the antisocial behaviors of football supporters. This mixed-method study employed survey, interview and observation as the data collection techniques. A total of 60 participants consisting of 10 stakeholders and 50 football supporters were involved in this study. The qualitative data were collected through structured interviews and field observations, while the quantitative data were obtained by administering questionnaires. The qualitative data analysis involved data display, data reduction, and conclusions, while quantitative data analysis using descriptive statistics and the mean difference test with one-way Anova. The results showed that the strategies to reduce antisocial behaviors of football supporters consisted of aggressive, religious, innovative, and fanaticism (ARIF) strategies. Stakeholders had six roles in an effort to reduce the antisocial behaviors of football fans, namely: supporting fans’ activities, giving ideas, consolidating with supporters, controlling, mediator, and giving consideration. These strategies and stakeholder roles were implemented through empowerment and education of the football supporters on a regular and ongoing basis so that antisocial behaviors change into good social behavior.